Exploring Fourth-Grade Students’ Perceptions of Genially-Integrated Interactive Learning Media in Science Education - Suryanto, Suryanto; Suryanti, Suryanti; Julianto, Julianto (IKIP PGRI Bojonegoro, 2025)
Interactive media can facilitate engaging and enjoyable learning experiences. One medium that meets these criteria is Genially-integrated interactive learning media. This study aims to explore students' perceptions of the use of Genially-integrated interactive learning media in science education. A descriptive quantitative approach was employed using a questionnaire distributed to 29 fourth-grade students. The questionnaire consisted of 12 statements covering aspects of student satisfaction, comfort, interest, and learning effectiveness. The collected data were analyzed using percentage criteria for perception scores. Results revealed that students responded positively to Genially-integrated interactive learning media, with a high level of agreement ranging from 83% to 90%. This favorable response is attributed to the media’s various interactive features, which enhance its functionality as a learning tool. The findings suggest that Genially-integrated interactive learning media can serve as a reference for classroom learning, particularly to boost student motivation and engagement.